Pre-asthma: a useful concept? A EUFOREA paper. Part 2—late onset eosinophilic asthma - G. K. Scadding; G. K. Scadding; C. Gray; C. Gray; D. M. Conti; D. M. Conti; M. McDonald; V. Backer; G. Scadding; M. Bernal-Sprekelsen; M. Bernal-Sprekelsen; E. De Corso; et al. (Frontiers in Allergy, 2024)
The concept of pre-diabetes has led to provision of measures to reduce disease progression through identification of subjects at risk of diabetes. We previously considered the idea of pre-asthma in relation to allergic asthma and considered that, in addition to the need to improve population health via multiple measures, including reduction of exposure to allergens and pollutants and avoidance of obesity, there are several possible specific means to reduce asthma development in those most at risk (pre- asthma). The most obvious is allergen immunotherapy (AIT), which when given for allergic rhinitis (AR) has reasonable evidence to support asthma prevention in children (2) but also needs further study as primary prevention. In this second paper we explore the possibilities for similar actions in late onset eosinophilic asthma.